Optical Resolution and Optimization of (R, S)‐Propranolol Using Dehydroabietic Acid Via Diastereomeric Crystallization. Issue 2 (29th October 2014) - Ge, Li; Zhao, Qiongqiong; Yang, Kedi; Liu, Shishi; Xia, Fan
Abstract The optical resolution of (R, S)‐propranolol by the diastereomeric crystallization method was successfully performed using dehydroabietic acid (DHAA) as the resolving agent in methanol. The three important parameters: DHAA amount, solvent (methanol) amount, and crystallization temperature of diastereomeric salts were optimized employing the response surface methodology (RSM). When maintaining a lower limit of 95% for the purity of (S)‐propranolol, the optimal resolution conditions were a DHAA/(R, S)‐propranolol molar ratio of 1.1, solvent/(R, S)‐propranolol ratio of 16.2 mL.g‐1, and crystallization temperature of –5 °C. The desired (S)‐propranolol was prepared with 94.8% optical purity and 72.2% yield under the optimal conditions. Chirality 27:131–136, 2015. © 2014 Wiley Periodicals, Inc.